IMPLEMENTATION OF BLOCKCHAIN FOR INCREASING TRACEABILITY AT VEHGRO SUPPLY CHAIN - Aprilio, Vito Ryan; Bergmans, Bettine (Diponegoro Journal of Accounting, 2020)
Blockchain is a new technology where the presence is emerging around many business sectors. Although the origin of blockchain was to facilitate business in financial sectors, the technology has developed to suit other sectors besides financial so that it can help the organization to be more effective and efficient. The technology which acts as a distributed ledger enables transparency in the usage. In the middle of current situation where consumer is deman ding more and more from an organization to provide information, even worst by some cases of food contamination, this new technology that originally creates for financial sectors has evolved to help business in the food sector and others. If implemented properly to the supply chain management of a business, it can be beneficial in many ways. This thesis aims to see the effectiveness and efficiency of the implementation of blockchain in VehGro company. The author used literature review as a research method which analysed scientific journals, reports, and research.